Lithium battery pack with anti-expansion structure
By adopting a corrugated structure panel and a thermal conduction frame with a layered composite structure in the lithium-ion battery pack, the shortcomings of the lithium-ion battery pack in thermal management and expansion force control are solved, and more efficient heat dissipation and safer battery pack structure are achieved. .
Patent Information
- Application Number
- CN202411305451.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-14
AI Technical Summary
The existing lithium-ion battery packs have shortcomings in thermal management and expansion force control, resulting in low heat dissipation efficiency, shortened battery life and increased safety risks.
A waveform structure panel formed by orthogonal lateral waves and longitudinal waves is used as an anti-expansion structure, and a multifunctional structural component is provided between the battery cells, including a thermal frame and an anti-expansion structure. The thermally conductive frame adopts a layered composite structure, including aluminum substrate and modified thermally conductive silicone, to improve heat dissipation efficiency.
Effectively control expansion force, improve heat dissipation efficiency, reduce the risk of thermal runaway, extend battery life and improve the overall performance and safety of the battery module.
Smart Images

Figure CN119447641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a lithium battery pack with an anti-expansion structure. Background Art
[0002] With the rapid development of new energy technologies, lithium-ion batteries have been widely used in electric vehicles, energy storage systems and other fields due to their advantages such as high energy density and long cycle life. However, there are still many challenges in the design and manufacturing process of lithium-ion battery modules, among which the most prominent ones are thermal management and expansion force control.
[0003] In terms of thermal management, water cooling and air cooling are currently the main methods used. Although the water cooling system has a significant heat dissipation effect, it is relatively expensive, so most battery modules still use air cooling to dissipate heat. However, the heat dissipation efficiency of the air cooling system is relatively low, and it is difficult to meet the heat dissipation requirements of high-power density battery modules, which may cause local overheating, thereby affecting battery performance and life.
[0004] In terms of expansion force control, the battery will expand in volume during the charge and discharge process, thereby generating interaction forces with the fixed structure. Moderate expansion force is conducive to the internal reaction of the battery, but excessive expansion force will cause excessive pressure on the battery, triggering lithium deposition and even irreversible capacity loss, seriously shortening the battery life.
[0005] At present, the industry mainly uses the following methods to alleviate the expansion force:
[0006] 1) Direct resistance method: Arrange the batteries closely and strengthen the external structure to directly resist the expansion force. However, as the battery capacity and the number of series connections increase, the expansion force also increases. This method is difficult to adapt to the needs of large-capacity and high-series battery modules.
[0007] 2) Buffer pad method: Add elastic buffer material between batteries to absorb part of the expansion force. However, this method will cause the battery to be in close contact with the buffer pad, limiting the heat dissipation channel and reducing the heat dissipation efficiency.
[0008] 3) Gap reservation method: Reserve gaps between batteries to allow the batteries to expand freely. However, this method may cause the battery to lack the necessary pressure in the initial stage, affecting the full electrochemical reaction, and also increasing the overall volume of the battery module.
[0009] In addition, existing expansion force mitigation structures generally have poor insulation and thermal conductivity. When thermal runaway occurs in a single cell, these structures are difficult to effectively prevent heat diffusion, which can easily lead to uneven temperature distribution inside the battery module, increasing the risk of fire or explosion.
[0010] In summary, the existing technology still has many deficiencies in solving the thermal management and expansion force control problems of lithium-ion battery packs. Therefore, it is urgent to develop a new battery pack structure that can effectively control the expansion force, improve the heat dissipation efficiency, and have good thermal runaway protection capabilities to improve the overall performance and safety of the battery module. Summary of the invention
[0011] The main purpose of the present disclosure is to provide a new battery pack structure that can effectively control the expansion force while improving the heat dissipation efficiency and having good thermal runaway protection capabilities to enhance the overall performance and safety of the battery module.
[0012] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0013] A lithium battery pack with an anti-expansion structure comprises a plurality of battery cells stacked in sequence, a multifunctional structural component is arranged between two adjacent battery cells, and the multifunctional structural component comprises a heat-conducting frame and an anti-expansion structure disposed inside the heat-conducting frame;
[0014] The anti-expansion structure includes a corrugated structure panel formed by orthogonal transverse waves and longitudinal waves, and the corrugated structure panel satisfies the following relationship:
[0015]
[0016] Wherein, x and y are the horizontal coordinates of each point on the corrugated structure panel along the x-axis and the vertical coordinates along the y-axis, respectively, and Z(x, y) is the normal coordinate of each point on the corrugated structure panel along the z-axis;
[0017] l, w are the length and width of the corrugated structure panel respectively; n x , n y are the number of wave peaks along the horizontal direction and the number of wave peaks along the vertical direction on the wave structure panel respectively; A is the amplitude of the waveform on the wave structure panel.
[0018] Preferably, the amplitude A of the waveform on the waveform structure panel is 1 to 5 mm.
[0019] Preferably, the anti-expansion structure is made of ceramic silicone foam, and the ceramic silicone foam includes the following components in weight proportion: 30-40 parts of vinyl silicone oil, 10-20 parts of white carbon black, 20-50 parts of nano-ceramic powder, 0.1-1.0 parts of ethynyl cyclohexanol, 1-10 parts of hydrogen-containing silicone oil, 1-10 parts of hydroxy silicone oil, 0.1-1.0 parts of platinum catalyst, 10-20 parts of β-eucryptite, and 1-8 parts of halloysite nanotubes.
[0020] Preferably, the heat-conducting frame comprises an enclosure formed by two side plates and two connecting plates.
[0021] Preferably, the thermally conductive frame is a layered composite structure, including an aluminum substrate and modified thermally conductive silica gel disposed on the surface of the aluminum substrate, and the thermally conductive frame is fixed to the battery cell via the modified thermally conductive silica gel.
[0022] Preferably, the preparation method of the modified thermally conductive silica gel comprises the following steps:
[0023] 1) Boron nitride and silane coupling agent are dispersed in 100 ml of aqueous solution at a mass ratio of 10:1, and the concentrations are 40 mg / ml and 4 mg / ml respectively; the mixed dispersion is placed in a water bath ultrasound, and after ultrasound for 40 minutes at 0°C, the excess solvent is removed by centrifugation, and the mixture is lyophilized to obtain modified boron nitride powder;
[0024] 2) Dispersing the modified boron nitride powder and graphene in a mixed solvent of alcohol and water in a ratio of 1:5, with concentrations of 1.2 mg / ml and 6 mg / ml, respectively, and adding 2 mg / ml carbon nanotubes at the same time, and ultrasonicating for 10 min at a power of 1200 W using an ultrasonic cell crusher to obtain a graphene slurry;
[0025] 3) immersing the polyurethane sponge foam in a 2 mol / L NaOH solution, treating it in 40° C. warm water for 3.5 h, and then placing it in a 5 mg / ml aniline methyl triethoxysilane aqueous solution and immersing it for 24 h to obtain a modified polyurethane porous foam;
[0026] 4) impregnating the modified polyurethane porous foam structure into the uniform graphene slurry prepared above, and ultrasonicating it in a water bath for 20 minutes at 0°C; drying it at 60°C, and then heating it from 60°C to 200°C at a heating rate of 15°C per minute, and then heating it from 200°C to 380°C at a heating rate of 3°C per minute for 30 minutes, removing the porous material, and obtaining a three-dimensional porous graphene-boron nitride composite material;
[0027] 5) The three-dimensional porous graphene-boron nitride composite material obtained above was immersed in silica gel, and the bubbles were removed by vacuum, and the composite material was placed in an oven at 125° C. and cured for 15 minutes to obtain a modified thermally conductive silica gel.
[0028] Preferably, the thermally conductive frame is a layered composite structure, including a first foam aluminum, a second foam aluminum and a third foam aluminum which are arranged in sequence from the inside to the outside, and the density ρ1 of the first foam aluminum, the density ρ2 of the second foam aluminum and the density ρ3 of the third foam aluminum satisfy the relationship: ρ1>ρ2>ρ3; and the first foam aluminum, the second foam aluminum and the third foam aluminum are all provided with an alternating pore structure, and the porosity Q1 of the first foam aluminum, the porosity Q2 of the second foam aluminum and the porosity Q3 of the third foam aluminum satisfy the relationship: Q1<Q2<Q3.
[0029] Preferably, the density ρ1 of the first foamed aluminum is 0.8-1.2 g / cm 3 The density of the second foam aluminum is ρ2 0.5-0.8 g / cm 3 The density of the third foam aluminum is ρ3 0.2-0.5 g / cm 3 ;
[0030] The porosity Q1 of the first foam aluminum is 45% to 60%; the porosity Q2 of the second foam aluminum is 60% to 75%; and the porosity Q3 of the third foam aluminum is 75% to 90%.
[0031] Preferably, the anti-expansion structure is made of foamed aluminum, and the density of the foamed aluminum is 0.2-0.5 g / cm 3 .
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] 1) The present invention adopts a corrugated structure panel formed by orthogonal transverse waves and longitudinal waves as an anti-expansion structure. By reasonably designing the geometric parameters of the corrugated structure panel, it can provide a moderate buffer force during the battery charging and discharging process, which can not only meet the appropriate pressure required for the internal reaction of the battery, but also effectively alleviate the excessive expansion force, thereby avoiding lithium precipitation and capacity loss caused by excessive pressure on the battery. Traditional expansion force mitigation methods either easily lead to excessive expansion force of the battery pack as a whole, or affect the heat dissipation efficiency or the adequacy of the battery reaction. The present invention arranges a corrugated structure panel with an anti-expansion structure between the battery cells, and utilizes the characteristics formed by the orthogonal transverse waves and longitudinal waves to absorb and disperse the expansion force, thereby avoiding direct rigid contact between the battery cells, thereby effectively reducing the negative impact of excessive expansion force on battery life.
[0034] 2) The present invention introduces a heat-conducting frame with good thermal conductivity, which not only effectively fixes the anti-expansion structure, but also improves the heat dissipation efficiency, thereby preventing the occurrence of thermal runaway and allowing the battery pack to maintain a low temperature under high-load working conditions, thereby extending the battery life and improving its safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a schematic structural diagram of a lithium battery pack in one embodiment of the present invention;
[0036] Figure 2 is a top view of a lithium battery pack in one embodiment of the present invention;
[0037] Figure 3 is a schematic structural diagram of a multifunctional structural component in one embodiment of the present invention;
[0038] Figure 4 is a top view of a multifunctional structural component in one embodiment of the present invention;
[0039] Figure 5 is a schematic structural diagram of an anti-expansion structure in one embodiment of the present invention;
[0040] Figure 6 is a schematic cross-sectional structure diagram of a heat-conducting frame in one embodiment of the present invention;
[0041] Figure 7 It is a schematic cross-sectional structure diagram of a heat-conducting frame in another embodiment of the present invention.
[0042] In the figure: 1. battery cell; 2. multifunctional structural component; 21. heat-conducting frame; 211. aluminum substrate; 212. modified heat-conducting silicone; 213. first foam aluminum; 214. second foam aluminum; 215. third foam aluminum; 22. anti-expansion structure. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Please see attached Figures 1 to 7 The present embodiment provides a lithium battery pack with an anti-expansion structure, comprising a plurality of battery cells 1 stacked in sequence, a multifunctional structural component 2 being arranged between two adjacent battery cells 1, the multifunctional structural component 2 comprising a heat-conducting frame 21 and an anti-expansion structure 22 disposed inside the heat-conducting frame 21;
[0045] The anti-expansion structure 22 includes a corrugated structure panel formed by orthogonal transverse waves and longitudinal waves, and the corrugated structure panel satisfies the following relationship:
[0046]
[0047] Wherein, x and y are the horizontal coordinates of each point on the corrugated structure panel along the x-axis and the vertical coordinates along the y-axis, respectively, and Z(x, y) is the normal coordinate of each point on the corrugated structure panel along the z-axis;
[0048] l, w are the length and width of the corrugated structure panel respectively; n x , n y are the number of wave peaks along the horizontal direction and the number of wave peaks along the vertical direction on the wave structure panel respectively; A is the amplitude of the waveform on the wave structure panel.
[0049] Among them, the anti-expansion structure 22 of the present invention adopts a corrugated structure panel formed by orthogonal transverse waves and longitudinal waves, and has isotropic properties; compared with triangular, unidirectional corrugated structures, it has higher energy absorption efficiency and anti-expansion buffering effect.
[0050] In one embodiment of the present application, the amplitude A of the waveform on the corrugated panel is 1-5 mm, so that the panel has sufficient elasticity to absorb the expansion force while maintaining the compactness of the battery spacing to optimize the internal space utilization and the stability between the battery cells.
[0051] In one embodiment of the present application, the length l of the corrugated structure panel is less than or equal to the length of the battery cell 1 ; the width w of the corrugated structure panel is less than or equal to the width of the battery cell 1 .
[0052] In one embodiment of the present application, the corrugated structure panel is prepared by 3D printing technology.
[0053] In one embodiment of the present application, the anti-expansion structure 22 is made of ceramic silicone foam, and the ceramic silicone foam includes the following components in weight proportions: 30-40 parts of vinyl silicone oil, 10-20 parts of white carbon black, 20-50 parts of nano-ceramic powder, 0.1-1.0 parts of ethynyl cyclohexanol, 1-10 parts of hydrogen-containing silicone oil, 1-10 parts of hydroxyl silicone oil, 0.1-1.0 parts of platinum catalyst, 10-20 parts of β-eucryptite, and 1-8 parts of halloysite nanotubes. The ceramic silicone foam provided by the present invention not only has good elasticity under normal working conditions and can provide good buffering and protection for battery cells; moreover, at high temperatures, the ceramic silicone foam can quickly form a foam ceramic body with a self-supporting structure and can maintain a high degree of pore structure retention rate, thereby exerting excellent heat insulation and flame retardant effects, and it can withstand the burning of flames above 1300°C for a long time, can effectively block the transfer of fire and temperature, and control the range of the fire within a single battery interval to avoid causing fires in adjacent batteries.
[0054] Among them, vinyl silicone oil is the main polymer matrix, which provides the required elasticity and flexibility in the foaming system; it can form a cross-linked structure by reacting with hydrogen-containing silicone oil, thereby enhancing the mechanical strength of the material. Silica is used as a reinforcing agent. Silica increases the tear strength and wear resistance of the composite material, while improving the compression resistance of silicone rubber, making the material less likely to deform even under higher loads. Nano-ceramic powder acts as a flame retardant. At high temperatures, nano-ceramic powder can promote the formation of a hard ceramic layer on the surface of the material, effectively preventing the further spread of flames and heat. Ethylene cyclohexanol is used as an inhibitor. This compound can control the rate of polymerization and avoid structural instability caused by too fast a reaction. Hydrogen-containing silicone oil acts as a cross-linking agent and reacts with vinyl silicone oil to form a silicone rubber network structure, enhancing the overall mechanical properties and thermal stability of the material. Hydroxyl silicone oil acts as a foaming agent in this system. Hydroxyl silicone oil decomposes and produces gas when heated to form a foam structure, thereby providing good cushioning properties and low density. Platinum catalyst catalyzes the addition cross-linking reaction of vinyl silicone oil and hydrogen silicone oil, improving the efficiency and uniformity of the reaction and ensuring the consistency of material performance. β-eucryptite, as a ceramic-forming agent, can promote the transformation of silicone rubber into ceramic body at high temperature, enhancing the high temperature resistance and structural stability of the material. Halloysite nanotubes, as a pore structure stabilizer, can form a uniformly distributed support structure in the material, enhance the stability of the pore structure, and avoid collapse under high temperature or mechanical pressure.
[0055] Therefore, through these specific components and their synergistic effects, the silicone foam of the present invention not only maintains excellent elasticity and flexibility, effectively protects the battery cells, but also significantly improves the performance of the material under extreme conditions. Especially in fire scenarios, the material can quickly form a self-supporting foam ceramic body, greatly improving the heat insulation and flame retardancy. This foam ceramic body can maintain its structural integrity and flame retardancy when subjected to high temperature or direct flame irradiation, unlike traditional silicone foam, which may crack, deform, collapse or even pulverize under the same conditions, thereby losing its protective ability.
[0056] The preparation method of ceramic silicone foam comprises the following steps:
[0057] Step S1, adding vinyl silicone oil, white carbon black, nano ceramic powder and β-eucryptite into a kneader, kneading into a mass at 100-150° C., cooling, and obtaining a base rubber;
[0058] Step S2, stirring and mixing the hydroxy silicone oil and the halloysite nanotubes to obtain a foaming mixture; wherein the stirring and mixing speed is 23000-26000 r / min, and the mixing time is 10-25 s;
[0059] Step S3, adding the foaming mixture, ethynyl cyclohexanol, hydrogen-containing silicone oil, and platinum catalyst into the base rubber, mixing evenly, to obtain a rubber material;
[0060] Step S4, vulcanizing and foaming the rubber material by using a casting, calendering or molding process to obtain ceramic silicone foam.
[0061] Among them, the ceramic silicone foam prepared by the present invention has the following advantages:
[0062] 1) Excellent mechanical properties and elasticity: Due to the cross-linked structure of vinyl silicone oil and hydrogen silicone oil, plus the reinforcement effect of white carbon black, the silicone foam of the present invention has good elasticity and resistance to mechanical stress, so that it can maintain its original shape and function after long-term use or repeated compression.
[0063] 2) Highly efficient flame retardant and heat insulation capabilities: The addition of nano-ceramic powder and β-eucryptite enables the material to quickly form a protective ceramic layer when exposed to high temperature or flame. This layer of structure can not only effectively isolate the flame, but also reduce heat transfer and protect the internal structure from damage.
[0064] 3) Highly stable foam structure: The foam structure is formed by the gas generated by the decomposition of hydroxy silicone oil, and its stability is enhanced by halloysite nanotubes, so that the foam is not easy to collapse even at high temperatures and maintains a high pore structure retention rate.
[0065] 4) Excellent heat resistance: The controlled polymerization rate of ethynyl cyclohexanol and the efficient catalytic effect of platinum catalyst ensure the uniform formation and stability of the silicone rubber network structure, thereby maintaining performance in extremely high temperature environments.
[0066] In one embodiment of the present application, the heat-conducting frame 21 includes a frame formed by two side plates and two connecting plates. The opening of the frame can be oriented in the up-down direction or in the left-right direction. Preferably, the opening of the frame is oriented in the left-right direction to facilitate the fixation of the anti-expansion structure 22. The frame structure formed by two side plates and two connecting plates can provide a good heat dissipation channel for the battery cell 1 while ensuring the stability of the battery module structure.
[0067] In one embodiment of the present application, the heat-conducting frame 21 is a layered composite structure, including an aluminum substrate 211 and a modified heat-conducting silicone 212 disposed on the surface of the aluminum substrate 211, and the heat-conducting frame 21 is fixed to the battery cell 1 through the modified heat-conducting silicone 212. The layered composite structure formed by the aluminum substrate 211 and the modified heat-conducting silicone 212 can effectively balance the heat conduction, buffering and bonding properties, wherein the modified heat-conducting silicone 212 can achieve a thermal conductivity of 6-10W / (m·k) through a specific preparation method, which can effectively improve the thermal conductivity of the heat-conducting frame 21, accelerate the heat conduction and dissipation of the battery cell 1, and effectively reduce the temperature gradient inside the battery module.
[0068] In one embodiment of the present application, a method for preparing the modified thermally conductive silicone 212 includes the following steps:
[0069] 1) Boron nitride and KH570 silane coupling agent are dispersed in 100 ml of aqueous solution at a mass ratio of 10:1, and the concentrations are 40 mg / ml and 4 mg / ml respectively; the mixed dispersion is placed in a water bath ultrasound, and after ultrasound for 40 minutes at 0°C, the excess solvent is removed by centrifugation, and the mixture is lyophilized to obtain a modified boron nitride powder;
[0070] 2) Dispersing the modified boron nitride powder and graphene in a mixed solvent of alcohol and water in a ratio of 1:5, with concentrations of 1.2 mg / ml and 6 mg / ml, respectively, and adding 2 mg / ml carbon nanotubes at the same time, and ultrasonicating for 10 min at a power of 1200 W using an ultrasonic cell crusher to obtain a graphene slurry;
[0071] 3) immersing the polyurethane sponge foam in a 2 mol / L NaOH solution, treating it in 40° C. warm water for 3.5 h, and then placing it in a 5 mg / ml aniline methyl triethoxysilane aqueous solution and immersing it for 24 h to obtain a modified polyurethane porous foam;
[0072] 4) impregnating the modified polyurethane porous foam structure into the uniform graphene slurry prepared above, and ultrasonicating it in a water bath for 20 minutes at 0°C; drying it at 60°C, and then heating it from 60°C to 200°C at a heating rate of 15°C per minute, and then heating it from 200°C to 380°C at a heating rate of 3°C per minute for 30 minutes, removing the porous material, and obtaining a three-dimensional porous graphene-boron nitride composite material;
[0073] 5) The three-dimensional porous graphene-boron nitride composite material obtained above was immersed in silica gel (Wacker SEMICOSIL9212), the bubbles were removed by vacuum, and the mixture was placed in an oven at 125° C. and cured for 15 minutes to obtain the modified thermally conductive silica gel 212.
[0074] In one embodiment of the present application, a method for preparing the modified thermally conductive silicone 212 includes the following steps:
[0075] 1) The open-cell polystyrene foam was immersed in a 20 wt % NaOH solution, treated in 40° C. warm water for 5 h, and then placed in a 2 mg / ml polyacrylamide solution for surface modification for 24 h, and then taken out for use.
[0076] 2) 40.5wt% of 120-mesh silicon carbide ceramic powder, 13.5wt% of graphene, 5wt% of alumina-yttrium oxide as a sintering aid, 30.5wt% of alcohol water as a solvent, 4wt% of sodium tetraborate as a binder, 4wt% of kaolin as a rheological agent, 2wt% of polyethyleneimine as a dispersant, and 0.3wt% of dimethyl silicone oil as a defoaming agent are used to prepare a graphene slurry.
[0077] 3) Immerse the surface-modified polystyrene foam in the slurry, ultrasonicate it in a water bath for 20 minutes, allow the slurry to fully enter the polystyrene foam, and dry it at 80°C. Expel the product obtained above under vacuum, set the temperature to rise from room temperature to 280°C at a heating rate of 15°C per minute, then heat from 280°C to 500°C at a heating rate of 3°C per minute for 30 minutes, and then quickly heat to 1700°C at 20°C per minute for 1 hour to obtain a three-dimensional porous graphene-silicon carbide material. The average size of the pores of the three-dimensional porous graphene-silicon carbide material was determined to be 2 to 4 mm, and the porosity was 75%.
[0078] 4) Place a mixed solution of 35wt% graphene and 85wt% silica gel in a degassing machine and stir for 30 minutes under cooling circulation conditions. The silica gel is AB type glue, namely Wacker SEMICOSIL 905A / B. After removing the bubbles, move it into a mold to obtain a mixed slurry, pour the mixed slurry into the three-dimensional porous graphene-silicon carbide material prepared above, and let it stand for one hour under vacuum conditions to allow the mixed slurry to fill the pores in the three-dimensional porous graphene-silicon carbide material, eliminate the bubbles, and then cure it at 120°C for 30 minutes to finally obtain modified thermally conductive silica gel 212.
[0079] In one embodiment of the present application, the thermally conductive frame 21 is a layered composite structure, including a first foam aluminum 213, a second foam aluminum 214 and a third foam aluminum 215 arranged in sequence from the inside to the outside, and the density ρ1 of the first foam aluminum 213, the density ρ2 of the second foam aluminum 214 and the density ρ3 of the third foam aluminum 215 satisfy the relationship: ρ1>ρ2>ρ3; and the first foam aluminum 213, the second foam aluminum 214 and the third foam aluminum 215 are all provided with an alternating pore structure, and the porosity Q1 of the first foam aluminum 213, the porosity Q2 of the second foam aluminum 214 and the porosity Q3 of the third foam aluminum 215 satisfy the relationship: Q1<Q2<Q3.
[0080] The layers can be formed into an integrated sheet structure by a hot pressing bonding process or a spraying process well known in the art.
[0081] Among them, the three-layer foam aluminum structure design with gradient density and porosity can effectively absorb and disperse impact energy, and has good thermal conductivity and heat dissipation effect, thus providing excellent buffer protection and thermal conductivity and heat dissipation performance. Among them, the first foam aluminum with high density and low porosity can first receive and disperse external impact energy, reducing the impact force directly transmitted to the inside; the second foam aluminum with medium density and high porosity can further absorb and disperse the remaining impact energy. The third foam aluminum with low density and high porosity has extremely high energy absorption capacity, which can eventually absorb and disperse the remaining impact energy to protect the battery cells. This application can achieve the effect of absorbing and dispersing impact energy layer by layer by innovatively combining the porosity and density of each layer, thereby significantly improving the buffer protection performance of lithium-ion battery packs. This gradient parameter design can provide comprehensive protection under different mechanical environments to ensure the safety and reliability of the battery pack.
[0082] In one embodiment of the present application, the density ρ1 of the first foamed aluminum is 0.8-1.2 g / cm 3 , preferably 0.95 g / cm 3 The density of the second foam aluminum is ρ2 0.5-0.8 g / cm 3 , preferably 0.65 g / cm 3 The density of the third foam aluminum is ρ3 0.2-0.5 g / cm 3 , preferably 0.35 g / cm 3 ;
[0083] The porosity Q1 of the first foamed aluminum is 45% to 60%, preferably 55%; the porosity Q2 of the second foamed aluminum is 60% to 75%, preferably 70%; the porosity Q3 of the third foamed aluminum is 75% to 90%, preferably 85%.
[0084] In one embodiment of the present application, the anti-expansion structure 22 is made of foamed aluminum, and the density of the foamed aluminum is 0.2-0.5 g / cm 3 , preferably 0.3 g / cm 3 Foamed aluminum is a new lightweight functional material that combines the characteristics of metal and bubbles. Its density is controlled at 0.2-0.5 g / cm 3 , which can make it have excellent energy absorption and buffering effect, effectively absorb the expansion force of the battery, and at the same time minimize the overall mass of the battery pack.
[0085] In one embodiment of the present application, the heat-conducting frame 21 is a layered composite structure, including an aluminum substrate 211 and a phase change material heat dissipation layer or a graphene heat dissipation layer disposed on the surface of the aluminum substrate 211. The phase change material heat dissipation layer or the graphene heat dissipation layer can be disposed on the surface of the aluminum substrate 211 by coating; in addition, the above-mentioned modified thermally conductive silicone 212 can be further disposed on the outer surface of the phase change material heat dissipation layer or the graphene heat dissipation layer.
[0086] In one embodiment of the present application, the phase change material is polyethylene glycol with an average relative molecular mass of 950 to 1050. When its phase change temperature (37 to 41° C.) is reached, a solid-solid phase change occurs, absorbing heat, reducing the surface temperature of the battery cell 1 and preventing thermal runaway of the battery pack.
[0087] In one embodiment of the present application, the phase change material includes sodium sulfate decahydrate, multi-walled carbon nanotubes, sodium carboxymethyl cellulose and polyvinyl alcohol, and the mass percentages of sodium sulfate decahydrate, multi-walled carbon nanotubes, sodium carboxymethyl cellulose and polyvinyl alcohol are 80-85%: 5-10%: 5-10%: 5-10%, preferably 85%: 5%: 5%: 5%. Among them, sodium sulfate decahydrate is used as the main phase change material, and its phase change temperature is moderate, with a high phase change latent heat, which can significantly absorb heat, thereby reducing the temperature of the battery pack; multi-walled carbon nanotubes can improve the thermal conductivity of the phase change material, ensure that the heat diffuses rapidly inside the material, and make the phase change process more uniform and efficient; sodium carboxymethyl cellulose, as a stabilizer, prevents the phase change material from crystallizing and phase separation during repeated use, and improves the mechanical strength and stability of the material; polyvinyl alcohol, as a dispersant, ensures that the multi-walled carbon nanotubes and other additives are evenly dispersed in the phase change material, prevents aggregation and sedimentation, and improves the overall performance of the material.
[0088] In one embodiment of the present application, the thermally conductive frame 21 is a layered composite structure, including an aluminum substrate 211 and a heat absorption and heat dissipation layer arranged on the surface of the aluminum substrate 211, and the heat absorption and heat dissipation layer includes the following components in weight proportions: 40 parts of aluminum nitride powder, 15 parts of cubic boron nitride powder, 5 parts of graphene nanosheets, 20 parts of polyimide resin, 5 parts of silane coupling agent, 10 parts of nano-grade silver powder and 5 parts of carbon nanotubes.
[0089] Among them, aluminum nitride, cubic boron nitride, graphene nanosheets, nano-scale silver powder and carbon nanotubes are used in combination, taking into account high thermal conductivity, high temperature resistance and mechanical strength. Among them, aluminum nitride and cubic boron nitride with high thermal conductivity enhance heat dissipation efficiency, graphene nanosheets and carbon nanotubes further improve thermal conductivity, and polyimide resin is used as a high temperature resistant matrix material, which works together with high thermal conductivity fillers to provide excellent heat dissipation performance and high temperature resistance. Silane coupling agent is used to modify the surface of the filler to improve the interface bonding between the filler and the matrix and enhance the comprehensive performance of the material. In addition, the components work synergistically to form an efficient thermal conductive network, which improves the thermal conductivity and heat dissipation performance of the thermal conductive frame.
[0090] The preparation method of the heat absorbing and heat dissipating layer is as follows:
[0091] Step 1: Pre-treatment
[0092] Materials preparation:
[0093] Aluminum nitride powder, cubic boron nitride powder, graphene nanosheets, nano-silver powder and carbon nanotubes are weighed according to proportions and set aside.
[0094] Polyimide resin and silane coupling agent are prepared.
[0095] Surface modification:
[0096] The fillers (aluminum nitride, cubic boron nitride, graphene nanosheets, nano-sized silver powder and carbon nanotubes) were mixed with a silane coupling agent in anhydrous ethanol and stirred for 2 hours for surface modification.
[0097] The modified filler was dried at 80 °C to remove the residual ethanol.
[0098] Step 2: Mixing and Dispersion
[0099] Mixed fillers:
[0100] Mix the modified fillers and use a high-speed stirrer or ball mill to ensure uniform dispersion; the mixing time is controlled to be more than 2 hours to ensure that all ingredients are fully mixed.
[0101] Add matrix material:
[0102] dissolving a polyimide resin in N-methylpyrrolidone (NMP) to form a uniform solution;
[0103] The mixed filler is gradually added to the polyimide solution and stirring is continued until a uniform slurry is formed.
[0104] Step 3: Molding and curing
[0105] The mixed slurry is evenly coated on the aluminum substrate 211;
[0106] The coated aluminum substrate 211 is dried at 80° C. for 2 hours to fully evaporate the NMP solvent;
[0107] Then, the aluminum substrate 211 is placed in an oven and cured at 300° C. for 2 hours to fully crosslink and cure the polyimide resin, thereby obtaining a heat absorbing and heat dissipating layer.
[0108] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0109] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A lithium battery pack with an anti-expansion structure, characterized in that: It comprises a plurality of battery cells stacked in sequence, a multifunctional structural component is arranged between two adjacent battery cells, and the multifunctional structural component comprises a heat-conducting frame and an anti-expansion structure disposed inside the heat-conducting frame; The anti-expansion structure includes a corrugated structure panel formed by orthogonal transverse waves and longitudinal waves, and the corrugated structure panel satisfies the following relationship: Wherein, x and y are the horizontal coordinates of each point on the corrugated structure panel along the x-axis and the vertical coordinates along the y-axis, respectively, and Z(x, y) is the normal coordinate of each point on the corrugated structure panel along the z-axis; l, w are the length and width of the corrugated structure panel respectively; n x , n y are the number of wave peaks along the horizontal direction and the number of wave peaks along the vertical direction on the wave structure panel respectively; A is the amplitude of the waveform on the wave structure panel.
2. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The amplitude A of the waveform on the waveform structure panel is 1 to 5 mm.
3. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The length l of the corrugated structure panel is less than or equal to the length of the battery cell; the width w of the corrugated structure panel is less than or equal to the width of the battery cell.
4. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The anti-expansion structure is made of ceramic silicone foam, which includes the following components in weight proportion: 30-40 parts of vinyl silicone oil, 10-20 parts of white carbon black, 20-50 parts of nano-ceramic powder, 0.1-1.0 parts of ethynyl cyclohexanol, 1-10 parts of hydrogen-containing silicone oil, 1-10 parts of hydroxy silicone oil, 0.1-1.0 parts of platinum catalyst, 10-20 parts of β-eucryptite, and 1-8 parts of halloysite nanotubes.
5. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The heat-conducting frame comprises a surrounding frame formed by two side plates and two connecting plates.
6. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The heat-conducting frame is a layered composite structure, including an aluminum substrate and modified heat-conducting silica gel arranged on the surface of the aluminum substrate, and the heat-conducting frame is fixed to the battery cell through the modified heat-conducting silica gel.
7. The lithium battery pack with an anti-expansion structure according to claim 6, characterized in that: The preparation method of the modified thermally conductive silica gel comprises the following steps: 1) Boron nitride and silane coupling agent are dispersed in 100 ml of aqueous solution at a mass ratio of 10:1, and the concentrations are 40 mg / ml and 4 mg / ml respectively; the mixed dispersion is placed in a water bath ultrasound, and after ultrasound for 40 minutes at 0°C, the excess solvent is removed by centrifugation, and the mixture is lyophilized to obtain modified boron nitride powder; 2) Dispersing the modified boron nitride powder and graphene in a mixed solvent of alcohol and water in a ratio of 1:5, with concentrations of 1.2 mg / ml and 6 mg / ml, respectively, and adding 2 mg / ml carbon nanotubes at the same time, and ultrasonicating for 10 min at a power of 1200 W using an ultrasonic cell crusher to obtain a graphene slurry; 3) immersing the polyurethane sponge foam in a 2 mol / L NaOH solution, treating it in 40° C. warm water for 3.5 h, and then placing it in a 5 mg / ml aniline methyl triethoxysilane aqueous solution and immersing it for 24 h to obtain a modified polyurethane porous foam; 4) impregnating the modified polyurethane porous foam structure into the uniform graphene slurry prepared above, and ultrasonicating it in a water bath for 20 minutes at 0°C; drying it at 60°C, and then heating it from 60°C to 200°C at a heating rate of 15°C per minute, and then heating it from 200°C to 380°C at a heating rate of 3°C per minute for 30 minutes, removing the porous material, and obtaining a three-dimensional porous graphene-boron nitride composite material; 5) The three-dimensional porous graphene-boron nitride composite material obtained above was immersed in silica gel, and the bubbles were removed by vacuum, and the composite material was placed in an oven at 125° C. and cured for 15 minutes to obtain a modified thermally conductive silica gel.
8. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The thermally conductive frame is a layered composite structure, including a first foam aluminum, a second foam aluminum and a third foam aluminum, which are arranged in sequence from the inside to the outside, and the density ρ1 of the first foam aluminum, the density ρ2 of the second foam aluminum and the density ρ3 of the third foam aluminum satisfy the relationship: ρ1>ρ2>ρ3; and the first foam aluminum, the second foam aluminum and the third foam aluminum are all provided with a staggered pore structure, and the porosity Q1 of the first foam aluminum, the porosity Q2 of the second foam aluminum and the porosity Q3 of the third foam aluminum satisfy the relationship: Q1<Q2<Q3.
9. The lithium battery pack with an anti-expansion structure according to claim 8, characterized in that: The density ρ1 of the first foamed aluminum is 0.8-1.2 g / cm 3 The density of the second aluminum foam is ρ2 0.5-0.8 g / cm 3 The density of the third foam aluminum is ρ3 0.2-0.5 g / cm 3 ; The porosity Q1 of the first foam aluminum is 45% to 60%; the porosity Q2 of the second foam aluminum is 60% to 75%; and the porosity Q3 of the third foam aluminum is 75% to 90%.
10. The lithium battery pack with an anti-expansion structure according to claim 1, characterized in that: The anti-expansion structure is made of foamed aluminum, and the density of the foamed aluminum is 0.2-0.5 g / cm 3 .
Citation Information
Patent Citations
Graphene heat conduction silica gel and preparation method thereof
CN106433131A
Efficient heat conducting material for CPU and preparation method of efficient heat conducting material
CN107151447A
Hyperbolic corrugated sandwich protection structure applied to plane pavement for arrest
CN107471756A
Functional gradient foamed aluminum and preparation method thereof
CN113667855A
Heat-conducting gasket and preparation method thereof
CN117210005A